Serum pharmacology of amphotericin B applied in lipid emulsions. - Heinemann, V (1997)
Application of amphotericin B in lipid emulsions (AmB/L) reduced membrane toxicity in vitro and decreased amphotericin B-associated toxic side effects in vivo when compared to that of amphotericin B applied in 5% glucose (AmB/G). Therefore, a comparative analysis of the pharmacological parameters of AmB/L and AmB/G was performed. Thirteen patients were analyzed, and nine of these patients received a subsequent treatment with AmB/G and AmB/L. In patients in both treatment groups amphotericin B showed a biphasic elimination from serum, with a prolonged terminal half-life of approximately 27 h. Patients treated with AmB/L showed significantly lower peak concentrations (44.2%; P = 0.008) and correspondingly lower area under the drug concentration-time curve (AUC) values (64.3%; P = 0.015) compared to the values for the same patients treated with AmB/G at a dose range of 0.6 to 1.5 mg/kg of body weight. The enhanced clearance of AmB/L may be due to a faster initial elimination of amphotericin B-lipid aggregates by the reticuloendothelial system. Lower peak concentrations and AUC values in serum and a correspondingly faster deposition of AmB/L in tissues may at least partly explain the lower toxicity of AmB/L. A comparative pharmacokinetic analysis with data for a single patient treated with AmB/L demonstrated that hemodialysis did not significantly affect the disposition of amphotericin B.